2019
DOI: 10.1002/biof.1554
|View full text |Cite
|
Sign up to set email alerts
|

Proline‐containing peptides—New insight and implications: A Review

Abstract: The family of regulatory proline‐containing peptides (PCPs), also known as glyprolines, exhibit significant biological activity. The group of glyprolines includes Gly‐Pro (GP), Pro‐Gly‐Pro (PGP), cyclic Gly‐Pro (cGP), as well as PGP derivatives, for example, N‐acetylated PGP (N‐a‐PGP) and N‐methylated PGP (N‐m‐PGP). PCPs are engaged in various biological processes including the proinflammatory neutrophil chemoattraction in lung diseases, inflammatory bowel diseases or ischemic stroke. Glyprolines have been als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…In kidney of streptotozin-induced diabetic mice and in diabetic patients, γ-Glu-ε-Lys seems to contribute to alterations in epithelial cell viability and tubular atrophy [ 35 ]. Alterations in dipeptide concentrations have been described for cancer [ 36 ], Parkinson disease [ 1 ], Alzheimer [ 37 ], Huntington disease [ 38 ], bronchopulmonary disease [ 39 ] or diabetes [ 35 , 40 ] and further studies in respective disease states are of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In kidney of streptotozin-induced diabetic mice and in diabetic patients, γ-Glu-ε-Lys seems to contribute to alterations in epithelial cell viability and tubular atrophy [ 35 ]. Alterations in dipeptide concentrations have been described for cancer [ 36 ], Parkinson disease [ 1 ], Alzheimer [ 37 ], Huntington disease [ 38 ], bronchopulmonary disease [ 39 ] or diabetes [ 35 , 40 ] and further studies in respective disease states are of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with carnosine or anserine prevented alterations of renal function in diabetic (db/db) mice [29][30][31]. Additionally, for proline-containing dipeptides the biological activities seem to be not only based on the free amino acid alone [1]; for Tyr-containing dipeptides [32] an inhibitory effect on ACE activity has been demonstrated, and Tyr-Asp improves plant tolerance to oxidative stress by directly interfering with glucose metabolism [33]. Gly-containing dipeptides can provide osmoregulation in preimplantation embryos [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New peptide preparations belonging to the class of glyprolins are becoming increasingly important. They contain GP, have increased metabolic stability, are involved in various biological processes, including the proinflammatory chemoattraction of neutrophils in lung diseases, inflammatory bowel diseases or in ischemic stroke 62 . One of the simplest glyprolins is the PGP peptide and studies have shown that the PGP peptide has antiulcer and anti‐inflammatory effects 63,64 .…”
Section: Peptide Regulation In Ischemic Conditionsmentioning
confidence: 99%
“…EGFR is a member of the transmembrane receptor tyrosine kinases (ERBB family) which requires dimerization of receptor subunits for autophosphorylation inducing further signaling [21,22]. This process leads to the induction of proliferation, differentiation, and migration of the cells through the phosphorylation of proteins in several signaling pathways [23][24][25]. The key EGFR downstream signaling involves the PI3K/AKT/mTOR, Ras/Raf/ERK, and JAK/STAT pathways [6,26,27].…”
Section: Introductionmentioning
confidence: 99%